A qualitative systematic review of barriers and facilitators to the implementation of community-based molecular diagnostics for infectious diseases. - Hannah Nelson; Jia Tong Song; Mai-Lei Woo Kinshella; Jennifer Cochrane; Karen Mooder; Kasra Hassani; Michelle Dittrick; David M Goldfarb (PLoS ONE)
Background Community-based molecular diagnostic testing for infectious diseases can bring equitable healthcare to resource-limited settings without hospital-based laboratories. Low-complexity molecular testing devices allow for unprecedented sensitivity and specificity for infectious disease diagnostics outside of a dedicated laboratory, which may facilitate timely initiation of therapeutics and other public health interventions in rural, remote and/or marginalized communities. Objective To identify barriers and facilitators to the implementation of community-based molecular testing. Methods A systematic search was conducted on MEDLINE Ovid, EMBASE, Web of Science, Cumulative Index to Nursing and Allied Health, Google Scholar, and reference lists. Original research that includes implementation of molecular testing systems at the community-level or at rural/remote health facilities with frontline healthcare workers and reports barriers and facilitators to implementation were included. Studies were assessed by the Critical Appraisal Skills Programme Qualitative Checklist and underwent inductive thematic analysis. The review protocol was registered to Prospero prior to conducting the review (CRD42023397800). Results A total of 6 studies were included in the review. We found three main themes present across all six included studies: infrastructure, usability, and staffing considerations. Infrastructure emerged as a critical determinant, with challenges ranging from physical space constraints to issues with reliable electricity and internet connectivity. The usability of testing devices, encompassing factors like ease of use and testing quality, also played a pivotal role. Staffing considerations, including workload, training, and attitudes, significantly influenced implementation outcomes. Conclusion Our review highlights the importance of addressing infrastructural challenges, ensuring usability of testing devices, and adequately supporting staff through training and workload management to realize the full potential of this new opportunity. Future implementation should consider these factors to successfully integrate molecular diagnostics into community-level healthcare delivery, particularly in rural and remote areas.